Cadaveric Specimens Used in Studies Evaluating Bone Loss in Anterior Shoulder Instability Are Not Representative of the Affected Patient Population: A Systematic Review - Amin Karimi, M.D.; Anya Singh-Varma, B.S.; Rajiv P. Reddy, M.D.; Matthew P. Kolevar, M.D.; Albert Lin, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To examine the age, sex, and site of evaluated bone loss in specimens used in cadaveric studies assessing the role of bone loss in anterior shoulder instability and to evaluate whether these studies evaluate glenoid and humeral bone loss separately or as a combined biomechanical problem. Methods: Embase, MEDLINE, Scopus, Web of Sciences, Google Scholar, and Cochrane databases were queried electronically in April 2023 for cadaveric studies examining the relationship between anatomic structures and recurrent anterior shoulder instability. The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria. Studies were excluded if they evaluated the role of soft tissue structures in anterior shoulder stability or assessed anterior bony reconstruction methods to create a stable shoulder and those with fewer than 5 specimens. The following search terms were used: cadaver(s), corpse(s), shoulder dislocation(s), glenohumeral dislocation(s), glenohumeral subluxation(s), glenoid (cavity), and humeral head. Data collected included the age, sex, and site of evaluated bone loss in cadaveric specimens. Studies were categorized based on the anatomic structure that was examined in connection with recurrent anterior shoulder instability: proximal humerus bone defects, glenoid bone defects, and combined bone defects. Results: Eighteen articles were included in the review, which evaluated 244 cadavers. The sex of 74 cadavers (30.3%) was recorded as male, 50 (20.4%) as female, and 120 (49.1%) were not reported. The mean age of the cadavers was 61.1 ± 15.9 years. Most of the investigations (55.5%) were conducted in the United States. Ten studies looked at the relationship between anterior shoulder instability and glenoid bony structure, 3 assessed the effect of Hill-Sachs lesion size, and only 5 (27.7%) investigated the impact of bipolar bone defects. Conclusions: The ages of cadavers utilized in biomechanical studies assessing the relationship of glenoid and humeral bone loss to anterior shoulder instability are different from the age range of patients who present with this clinical problem. Males were more frequently studied, and most of these biomechanical studies were conducted in the United States. In addition, few studies evaluate the relationship between anterior shoulder instability and bone loss as a bipolar structural defect. Clinical Relevance: It is important to understand how closely study specimens match the patient population with the condition being investigated. This study will provide information about the cadaveric specimens used in studies evaluating bone loss in anterior shoulder instability.